The Responsibility to Protect norm cluster and the challenge of atrocity prevention: an analysis of the European Union's strategy in Myanmar. (September 2020) - Staunton, Eglantine; Ralph, Jason
This article investigates the complex relationship between atrocity prevention and other related – yet distinct – norms of the Responsibility to Protect (R2P) norm cluster. It analyses how this cluster operates to help states, and other actors, properly discharge their responsibility. Central to the analysis is the realisation that abstractly aligned norms can clash in practice. Based on an extensive analysis of the 67 European Union (EU) documents and statements referring to R2P, and drawing on elite interviews with EU diplomats, we find that atrocity prevention has been 'grafted' onto the EU's other normative commitments – including conflict resolution and democracy promotion – without sufficient acknowledgement of the cluster's complexity and the need to prioritise atrocity prevention vis-à-vis these other linked norms. We ask whether this framing not only filtered but also diluted the normative power of atrocity prevention, leading to policies that manifestly failed to prevent the genocide that occurred in Myanmar from 2017. We find that the grafting of atrocity prevention onto related yet distinct norms contributed to an underestimation of the threat of genocide and a misplaced faith in the ability of democratic transition to prevent atrocity. However, we also find that factors unrelated to the normative framing of R2P influenced the EU's willingness and ability to respond to atrocity crimes that occurred in the lead up to the genocide that began in 2017. The article contributes to our understanding of the as yet unstated normative implication of clustering norms and the EU's implementation of R2P.